STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT SMPN 1 BLANGPIDIE - Nurul Fazilah (Yayasan Nusantara Hasana Berdikari, 2025)
The problem in this study is how students' abilities in writing descriptive texts. The purpose of this study is to describe students' ability in writing descriptive texts. This study is a descriptive quantitative research with the total sample of 32 students of VII A class at SMPN 1 Blangpidie. The descriptive analysis indicate that most students are not able to write English descriptive texts. The results of the study also indicate that most students fall into 'unable' category (62.5%). Further information on the encountered challenges are discussed in the article.